2018
DOI: 10.1016/j.jhep.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Supportive and palliative care in people with cirrhosis: International systematic review of the perspective of patients, family members and health professionals

Abstract: Patients and their families had a poor understanding of advanced liver disease and its impact on them. They need more information about the treatments they receive and how to get practical and psychological support. Liver specialists and GPs found it difficult to talk to patients and their families about the seriousness of advanced liver disease and the lack of healthcare options available to them if their condition gets worse. All doctors and nurses involved in the care of patients with advanced liver disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 40 publications
2
76
2
6
Order By: Relevance
“…Low et al conducted a systematic review of 19 studies reporting health care professionals' perspectives on supportive and palliative care. 45 Liver health care professionals lacked confidence and skills in discussing patients' prognoses, disease progression, and treatments, despite identifying these as information needs. They tended not to address symptom or quality of life problems unless patients raised these.…”
Section: Current Barriers To Accessing Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Low et al conducted a systematic review of 19 studies reporting health care professionals' perspectives on supportive and palliative care. 45 Liver health care professionals lacked confidence and skills in discussing patients' prognoses, disease progression, and treatments, despite identifying these as information needs. They tended not to address symptom or quality of life problems unless patients raised these.…”
Section: Current Barriers To Accessing Palliative Carementioning
confidence: 99%
“…15 A systematic review by Low et al emphasized patient's lack of understanding about their disease trajectory and prognosis, often lacking awareness of the palliative nature of the disease and perceiving communication with health care professionals as poor. 45 This is compounded by the fact that patients with end-stage liver disease are more likely to be socially deprived, with poor access to health care services overall. 7, 49 The unpredictable nature of patients' disease trajectories is further compounded by a lack of validated tools to identify patients who would benefit from referral to palliative care.…”
Section: Current Barriers To Accessing Palliative Carementioning
confidence: 99%
“…The complex clinical management of advanced liver disease in addition to the functional impact of cirrhosis on activities of daily living and quality of life may result in patients with unmet practical and psychological needs. [11][12][13] In this study, we refer to the term "supportive needs" as encompassing patients' perceived needs for management of symptoms, general physical and psychological health, spiritual, practical, physical, social, sexual, information, and cultural needs. 11,14 Many patient-reported outcome measurements have been developed to evaluate specific areas and levels of need to guide patient care in the area of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In this study, we refer to the term "supportive needs" as encompassing patients' perceived needs for management of symptoms, general physical and psychological health, spiritual, practical, physical, social, sexual, information, and cultural needs. 11,14 Many patient-reported outcome measurements have been developed to evaluate specific areas and levels of need to guide patient care in the area of chronic diseases. For example, there are several disease-specific patient-reported measurements that assess needs in neurological conditions 15,16 and cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, good communication is often difficult to implement. This is highlighted in the case of delivering health care to people with cirrhosis (2), where a limited number of studies have shown inadequate doctor-patient communication (3), in which consultation times are too short for effective information exchange (2) and with too much focus on disease modification (2,4). Patients feel stigmatized when communicating with health professionals (5) because of the association of liver disease with substance misuse (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%